Korelasi short form-36 dengan skala eastern cooperative oncology group dalam menilai kualitas hidup pada pasien limfoma non hodgkin yang mendapat kemoterapi regimen cyclophosphamide, doxorubicin, vincristine, dan prednisone - Dika Iyona Sinulingga; Savita Handayani; Dairion Gatot (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Introduction : Health-related quality of life’s (HRQOL) assessment has become a vital tool. In this study, we analyze two generic instruments ECOG Scale and SF-36 in NHL patients receiving CHOP chemotherapy. This study intends to find out the the correlation between SF-36 and ECOG scale in NHL patients receiving CHOP chemotherapy.Method : Cross sectional research was conducted from October 2012 up to December 2013. Samples were selected consecutively to NHL patients. SF-36 and ECOG scale was assessed after CHOP chemotherapy cycle 6.Results : There were 21 patients of NHL, 12 male, 9 female, age 20 – 64 years old, mean 47.95 (SD 10.85). The range score of SF-36: 23.9 – 95.9, mean 75,3 (SD 17.93). The range scale of ECOG 0 – 4, mean 0.81 (SD 1.12). By using Spearman correlation, we found a significant correlation between SF-36 and ECOG scale (r = - 0.744, p = 0.0001). SF-36 showed good diagnostic performance to predict good ECOG scale with cut-off •'3d 54.66, with sensitivity 94.7%, specificity 100%, PPV 100%, NPV 66.67%, LR (+) ~, LR (-) 0.05, accuracy 95.23%, and AUC 98.7% (95% CI: 0% - 100%; p = 0.027).Conclusion : SF-36 correlates with ECOG scale and has a very good diagnostic in predicting ECOG scale.Key word : SF-36; ECOG scale; Quality of life; Non Hodgkin Lymphoma; CHOP chemotherapy